EDUKASI TERHADAP PELAJAR SEBAGAI UPAYA PENCEGAHAN MENJADI KORBAN CURANMOR DI LINGKUNGAN SEKOLAH - Rinaldi, Kasmanto; Putri, Poppy Amanda; Risani, Dwi Isprianti; Zubaini, Fenty; Viero, Diel; Tazam, Zikrul Yaumul; Aprinianto, Rifky (Komunitas Manajemen Kompetitif, 2023)
The occurrence of motorbike theft crimes can occur anywhere, including schools. School students can also be victims. Students who drive motorbikes to school are vulnerable to becoming victims of theft. This topic was chosen because based on the results of observations in the field, many high school (SMA) students parked their motorbikes carelessly at school. Motorbike theft occurs mostly because it is triggered by the negligence of the victim. Students who bring motorbikes to school are certainly the right target for perpetrators due to minimal guarding and security. The socialization method uses two stages, namely the preparation and implementation stages and the delivery of material through the method of delivering material. The result is that students must know the role of the victim in the occurrence of motorbike theft crimes and understand how to avoid these crimes. Therefore this socialization is carried out to provide education to students so that they do not become victims of motorbike theft crimes in their school environment.